Strategi Penerapan Fungsi Spesialisasi Pertambangan Dalam Program Dual Career Path di PT Freeport Indonesia - Sirait, Julius Iskandar; Maarif, M. Syamsul; Baga, Lukman M. (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to analyze retention conditions based on the turnover rate of permanent employee in the last 10 years, identify potential mining technical specialization professions, and determine operational division that primarily needed in implementing the mining specialization function as well as alternative strategy for implementing the mining specialization function. This study uses quantitative methodological analysis approach based on turnover rate calculation, labor gap identification, and Analytical Hierarchy Process (AHP) processed in Super Decision v. 2.10 software application. The determination of mining specialization profession is done by qualitative methodological analysis approach. As a result, PTFI's permanent employee turnover rate tends to increase in 2020 reaching 2,4%, and the mining specialization profession can be applied to as many as 24 job codes based on the Indonesian Standard Position Classification. Geoengineering division has a primary need in implementing the mining specialization function with the dominance of permanent workers who leave reaching 67,9% and have an educational background of S1 for geology, hydrology and geotech engineer professions. The final result of this study shows in the opinion of three selected experts that the main priority of the strategy for implementing the mining specialization function in the DCP at PTFI is determining qualifications, followed by strategies in the form of career planning, training, education, and candidate selection, with also providing remuneration for mining specialization workers. Keywords: AHP, dual career path, mining specialization function, strategy, turnover